2017
DOI: 10.21107/jaffa.v5i2.3408
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Tendency of Fraud in Government Sector

Abstract: <p>The purpose of this study is to explore perception of government officials in government agencies about the effects of morality of individuals, organizational culture, and leadership style on tendency of fraud. This study is a quantitative research using a survey which collected main data from the samples by using questionnaire. This research was analyzed with Multiple Linear Regression Analysis. The respondents of this research were the Subsection Head of Finance and Expenditure Treasurer. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…There are many past research (N'Guilla Sow, Basiruddin, Mohammad, et al, 2018;Tazilah & Hussain, 2015) that study on the effect of internal control in small companies like SMEs. Thus far, previous study (Fernandhytia & Muslichah, 2020;Lestari et al, 2017;Setiawan, 2018) has shown a negative relationship between the internal control and accounting fraud tendency. Most of these studies only provided evidence specifically on accounting fraud not generally on occupational fraud.…”
Section: Internal Control and Occupational Fraud Tendencymentioning
confidence: 96%
See 1 more Smart Citation
“…There are many past research (N'Guilla Sow, Basiruddin, Mohammad, et al, 2018;Tazilah & Hussain, 2015) that study on the effect of internal control in small companies like SMEs. Thus far, previous study (Fernandhytia & Muslichah, 2020;Lestari et al, 2017;Setiawan, 2018) has shown a negative relationship between the internal control and accounting fraud tendency. Most of these studies only provided evidence specifically on accounting fraud not generally on occupational fraud.…”
Section: Internal Control and Occupational Fraud Tendencymentioning
confidence: 96%
“…Several studies have been done to examine causes for occupational fraud tendency in companies. Nevertheless most had focused on accounting fraud tendency which is part of occupational fraud as seen in Fernandhytia & Muslichah (2020); Lestari et al (2017); Putri & Irwandi (2017) and excluded asset misappropriation. Several other studies have examined occupational fraud cases from the perspective of public listed companies and public sector, while excluded SMEs in their sample as seen in (Gunasegaran et al, 2018;Omar et al, 2016;Mohamed et al, 2017).…”
Section: Problem Statement and Objectivesmentioning
confidence: 99%
“…One possible reason for that was because in this study the definition of educational background was only about the level of education. The high morality of individuals can be seen from the participation of the respondents in the course/training/ technical guidance in the field of accounting (Lestari et al, 2017). Having an educational background based on the type of business and industry can increase the directors' knowledge in business continuity (Kusumastuti et al, 2007).…”
Section: Overall Model Fit Testmentioning
confidence: 99%
“…Audit of investigation [7] [8]. However, unlike [9], which demonstrates that investigative audits have no influence on fraud disclosure. Forensic accounting [3] has an effect on fraud disclosure variables, but varies from [10] and [11] in that it does not have an effect on fraud disclosure.…”
Section: Introductionmentioning
confidence: 99%